Internet of Things based architecture for additive manufacturing interface. (24th December 2021) - Phang, Swee King; Ahmad, Norhijazi Bin; Aravind, Chockalingam Vaithilingam; Chen, Xudong
The traditional process of selecting 3D printers and monitoring printing statuses manually has presented a big flaw in the additive manufacturing system as it requires physical interaction between the machines and humans. In this paper, a solution to zero physical interaction to additive manufacturing units is proposed. The objective is achieved by using the saturated IoT technologies. Webserver will be used to create a webpage to upload the file, approval, and check the printing status. A server will be used to store the files, slicing software, files queuing system and to store temporary information of the manufacturing units' status. Cameras on multiple 3D printers will be used as sensors to monitor the project progress visually. The proposed system is implemented and verified in the Additive Manufacturing Laboratory at Taylor's University Malaysia.